Fenomena Doktrin Virtual Masa Kini Berdasarkan Kajian Teologis Kritis Matius 23:13-33 - Sumiyati Sumiyati; Carolina Etnasari Anjaya (Sekolah Tinggi Teologi Arastamar Bengkulu, 2022)
True doctrine contains real energy and events as a character-spirit changer of listeners. When the doctrine taught is not put into practice by the preacher then the doctrine is not real or virtual, because it does not impartation and is powerless to change. This study aims to describe the meaning of virtual doctrine based on a study of Matthew 23:13-33 and its impact on the development of the Christian faith. The research method uses a qualitative approach with literature study and interpretation of the biblical text. Data were also obtained through direct observation and interviews in the field. The results of the study conclude that the phenomenon of virtual doctrine can have a fatal impact on the development of the congregation's faith. Therefore, spiritual leaders need to reflect and change themselves so that they are able to live the teachings they convey and in the end can become living examples.